PP.17.31: BLOOD PRESSURE/HEART RATE VARIABILITY IN HOME BLOOD PRESSURE MONITORING. (June 2015) - Kempny, P.; Gonzalez, S.; Castellaro, C.; Forcada, P.; Svane, J. Chiabaut; Obregon, S.; Kotliar, C.
Abstract : Objective: The effect of mean blood pressure levels on arterial stiffness development is well known; however, the role of dynamic factors as autonomic dysfunction (AD) over the pulse wave velocity (PWV) in the mid-term is still under evaluation. Objectives: a) To evaluate the contribution of home blood pressure (BP) and heart rate (HR) variability to assess arterial stiffness in essential hypertension (EH). b) To determinate if autonomic dysfunction (increased BP variability and decreased HR variability) is associated to higher PWV. Design and method: We evaluated 202 consecutive hypertensive patients who assist to be evaluated in a primary cardiovascular prevention program. All patients underwent anthropometric measurements. BP and HR were recorded through home BP monitoring/ 7 consecutive days (MicroLife®). Measurements of PWV were carried out using an automatic oscillometric device (Mobil-O-Graph®) at rest. We defined an autonomic dysfunction index (ADI) as follows: -ADI: standard deviation of systolic BP (SBP_SD)/standard deviation of HR (HR_SD) Correlations between mean systolic BP, SBP_SD, HR_SD and ADI with PWV were performed. Results: After applying exclusion criteria 120 patients with EH (135 ± 14/90 ± 10 mm Hg, 55 +/-10 years, 74% male, 107 treated) were included. Mean SBP was associated with PWV (r=0.23, p: 0.01) while SBP_SD showed a higher direct association with PWV (r = 0.32, P < 0.0003), unlike HR_SD (r = -0.20, P = 0.03). The index of autonomic dysfunction –ADI- presented the more significant association with PWV (r = 0.43, p < 0.0001). Figure. No caption available. Conclusions: Home SBP variability showed a higher and direct association than mean SBP values with PWV in EH. The AD phenomenon (expressed as higher BP variability/ lesser BP variability) presented a close positive relationship with PWV, which could indicate some role of mid-term AD in the increment of PWV in essential hypertension.